Studi Ekonomi Pemanfaatan Sumberdaya Ikan Karang Konsumsi di Kabupaten Sikka, Nusa Tenggara Timur - Bhokaleba, Barnabas Pablo Puente Wini; Fahrudin, Achmad; Adrianto, Luky (Universitas Brawijaya, Indonesia, 2015)
This research aimed to determine the feasibility of fishing of reef fish for consumption and optimum utilization of reef fish. This research conducted at Sikka District using primary and secondary data. The analysis used in this study using the proposed feasibility (Kadariah et.al, 2001) and the Bioeconomic analysis by Clark, Yoshimoto and Pooley (1992). Businesses reef fishing is using fishing gear, gill nets and traps remain profitable and feasible to be developed because of the NPV Rp38,414,136.75, Rp44,403,139.89 and Rp1,893,186.47; IRR 111%, 61% and 22 %, and the value of net Benefit-Cost 12.64, 5.30, and 1.19. Optimal exploitation of biological of reef fishery management were 1,907,168 fishing effort, 397.18 ton per year production and Rp3.782.990.000 economic rent per year. While the optimum economic exploitation of reef fishery management were 1,537,262 fishing effort, 382.24 ton per year productions and Rp4.015.500.000 economic rent per year. Although reef fishing business benefits but the exploitation rate carried out by fishers had dedicated over exploitation so that government policy to limit the fishing effort should be imposed.